Infectious etiology of intussusception in Indian children less than 2 years old: a matched case-control analysis - Ira Praharaj; Samarasimha Nusi Reddy; Nayana Prabhakaran Nair; Jacqueline Elizabeth Tate; Sidhartha Giri; Varunkumar Thiyagarajan; Venkata Raghava Mohan; Rajendiran Revathi; Kalaivanan Maheshwari; Priya Hemavathy; Nirmal Kumar; Mohan Digambar Gupte; et al. (Gut Pathogens)
Abstract Background Enteric infections are hypothesized to be associated with intussusception in children. A small increase in intussusception following rotavirus vaccination has been seen in some settings. We conducted post-marketing surveillance for intussusception following rotavirus vaccine, Rotavac introduction in India and evaluated association of intussusception with enteric pathogens. Methods In a case-control study nested within a large sentinel hospital-based surveillance program in India, stool samples from 272 children aged less than 2 years admitted for intussusception and 272 age-, gender- and location-matched controls were evaluated with Taqman array card based molecular assays to detect enteric viruses, bacterial enteropathogens and parasites. Matched case-control analysis with conditional logistic regression evaluated association of enteropathogens with intussusception. Population attributable fractions (PAF) were calculated for enteropathogens significantly associated with intussusception. Results The most prevalent enteropathogens in cases and controls were enteroaggregative Escherichia coli, adenovirus 40/41, adenovirus C serotypes and enteroviruses. Children with intussusception were more likely to harbor adenovirus C serotypes (adjusted odds-ratio (aOR) = 1.74; 95% confidence interval (CI) 1.06–2.87) and enteroviruses (aOR = 1.77; 95% CI 1.05–2.97) than controls. Rotavirus was not associated with increased intussusception risk. Adenovirus C (PAF = 16.9%; 95% CI 4.7% − 27.6%) and enteroviruses (PAF = 14.7%; 95% CI 4.2% − 24.1%) had the highest population attributable fraction for intussusception. Conclusion Adenovirus C serotypes and enteroviruses were significantly associated with intussusception in Indian children. Rotavirus was not associated with risk of intussusception.